Adult Onset Still's Disease: A Case Report - Siddiqui, Mahmudur Rahman; Khan, Golam Kibria; Islam, Md. Safiqul; Ahmed, KM Ahasan (Anwer Khan Modern Medical College Journal, 2013)
Adult onset Still's disease (AOSD) is a chronic multi-system inflammatory disorder characterized by high spiking fever, polyarthralgia and skin rash. Lymphadenopathy is another prominent feature of adult onset Still's disease. We describe a 22 years old lady presented with fever, skin rashes and polyarthritis for 3 months. Examination revealed fever, typical skin rash, generalized lymphadenopathy and polyarthritis. On investigation there were neutrophilic leukocytosis, high ESR, high ferritin level, but RA test and ANA test were negative. All of her history, clinical examinations and laboratory findings fulfill the diagnostic Yamaguchi criteria for AOSD. With proper treatment, now she is completely symptoms free and leaving a healthy life. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 52-54 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16944